Organic-walled dinoflagellate cysts from the Eocene-Oligocene Transition in the Gulf of Mexico: indicators of climate- and sea-level change during the onset of Antarctic glaciation - Houben, AJP; Quaijtaal, W; Wade, BS; Schouten, S; Brinkhuis, H (Schweizerbart und Borntraeger, 2019)
The Eocene – Oligocene Transition (EOT, ∼34–33.5 Ma) marks a major transition in Cenozoic climate evolution through the relatively rapid establishment of a continental-scale ice sheet on Antarctica. The EOT is characterized by two ∼200 kyr spaced shifts (termed EOT-1 and Oi-1) in the oxygen isotopic composition (σ18O) of benthic foraminifera, representing both changes in continental ice-volume and temperature. Estimates of the timing and magnitude of these changes during this critical phase in Earth’s climatic evolution are controversial. Here we present marine palynological assemblage data, in particular of organic-walled dinoflagellate cysts (dinocysts), across a classic upper Eocene to lower Oligocene neritic succession cored in Alabama, USA; the Saint Stephens Quarry (SSQ) borehole. These palynological data combined with lithological information allow the identification of three sequence boundaries across the EOT. Critically, we identify a sequence boundary at the level corresponding to the EOT-1. Integrated sea level and paleotemperature records show that EOT-1 primarily represents cooling with some minor and transient continental ice sheet expansion. Furthermore, we identify a significant hiatus, likely caused by major sea level fall at the base of Magnetochron C13 n that corresponds to the Oi-1 shift. This clarifies the σ18O records from SSQ that essentially lack the expected pronounced shift to positive σ18O values so characteristic for Oi-1. Furthermore, we document originations and extinctions of potentially temperature-sensitive dinocysts associated with the EOT-1. In contrast, the Oi-1 does not stand out as period of substantial dinoflagellate turnover. The combined results illustrate that major cooling, limited and transient ice growth and major biotic change were occurring before the full-size expansion of the Antarctic cryosphere.